Optimalisai Pertumbuhan dan Hasil Tanaman Sorgum (Sorghum bicolor (L.) Moench) dengan Aplikasi Biosaka dan Pupuk NPK di Lahan Pasca Tambang Timah - Lestari, Tri; Niswarni, Annisa; Pratama, Deni (Seminar Nasional Lahan Suboptimal, 2024)
Lestari, T., Niswarni, A., & Pratama, D. (2024). Optimization of growth and yield of sorgum (Sorghum bicolor (L.) Moench) plant with application of biosaka and NPK fertilzer on post-tin mining land. In: Herlinda S et al.(Eds), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 580-590). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Post-tin mining land is land that is low in nutrients. The low nutrient content causes the land to not be used optimally. Sorghum plants are one alternative to be developed in post-tin mining land. Sorghum plant growth and yield can be optimized by providing biosaka and NPK fertilizer. The research was conducted from January to June 2024. The research location was in the Kampoeng Reclamation Air Jangkang land, Merawang District, Bangka Regency. This study used an experimental method with a Randomized Block Design (RAK) split splot consisting of 2 plots. The main map is without biosaca (A0) and biosaca and (A1), and the sub-plot of NPK use consisting of 4 levels, namely without NPK fertilizer (B1), 50% NPK (B2), 75% NPK (B3), and 100% NPK (B4). The results of the analysis of post-mining land soil have acidic pH soil content, C-Organic content, N-total in the very low category, with high sand content reaching 96%, and very low dust and clay content of 2%. The results of the study showed that the application of biosaca and NPK fertilizer did not show any interaction with all observed variables . Biosaca application on sorghum plants showed no effect on the observed variables. The use of various doses of NPK fertilizer treatment showed a very significant effect on the variables of plant height, wet weight of the crown and wet weight of the roots, and also affected the variables of stem diameter and panicle length. Treatment without biosaca and 100% NPK fertilizer produced better results compared to treatment with biosaca administration.